Triple bond rigidified anthracene-triphenylamine sensitizers for dye-sensitized solar cells. (August 2019) - Yoosuf, Muhammed; Pradhan, Sourava C.; Soman, Suraj; Gopidas, Karical R.
Graphical abstract: Highlights: Two anthracene appended triphenylamine dyes TPAA6 and TPAA7 were synthesized. An efficiency of 3.56 ± 0.05% for TPAA6 and 4.38 ± 0.1% for TPAA7 was obtained. TPAA7 achieved better light harvesting capabilities compared to TPAA6. The propeller shaped architecture helped in preventing aggregation for both dyes. Successfully eliminated the use of co-adsorbents like CDCA. Abstract: Two anthracene bridged triphenylamine sensitizers TPAA6 and TPAA7 were designed, synthesized and used as potential candidates for dye-sensitized solar cells. Investigations on structure-property relationship, photophysical, electrochemical and device dynamics were explored in detail. Absorption spectra revealed that both the dyes are capable of harvesting light up to 600 nm with properly positioned ground and excited states for efficient electron injection and regeneration. The current density-voltage ( J-V ) characteristics under one sun illumination revealed a power conversion efficiency of 3.56 ± 0.05% for TPAA6 and 4.38 ± 0.1% for TPAA7. IPCE plots were in accordance with the J-V data. The improvement in current density and voltage for TPAA7 was mainly attributed to the improved lifetime which was studied in detail by employing various perturbation techniques.